2019
DOI: 10.1002/advs.201802135
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine α‐Phase Molybdenum Carbide Decorated with Platinum Nanoparticles for Efficient Hydrogen Production in Acidic and Alkaline Media

Abstract: The development of efficient electrocatalysts is important to produce clean and sustainable hydrogen fuel on a large scale. With respect to cathodic reactions, Pt exhibits an overwhelming electrocatalytic capability in the hydrogen evolution reaction (HER) in comparison with other earth‐abundant electrocatalysts, despite its rarity and high cost. So, a hybrid catalyst that combines a low‐cost electrocatalyst with Pt would balance cost‐effectiveness with catalytic activity. Herein, α‐phase molybdenum carbide (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…283.7 eV is distinctly found in Fig. 1 (e), which can be assigned to the Mo-C bond in cubic MoC [40] . From Fig.…”
Section: Strategy For the Synthesis Of Tio 2 /Moc@cmentioning
confidence: 82%
See 1 more Smart Citation
“…283.7 eV is distinctly found in Fig. 1 (e), which can be assigned to the Mo-C bond in cubic MoC [40] . From Fig.…”
Section: Strategy For the Synthesis Of Tio 2 /Moc@cmentioning
confidence: 82%
“…More importantly, it was reported that cubic MoC clearly has a higher electrical conductivity because the electrical resistivity of cubic MoC (4.9 μ cm at 20 °C) is much lower than that of hexagonal Mo 2 C (97.5 μ cm at 20 °C) [39] . In fact, cubic molybdenum carbide had been demonstrated as an active and stable electrocatalyst for high electrocatalytic H 2 -evolution performance [40] . On the basis of their similar H 2 -evolution mechanism between electrocatalysts and photocatalysts, it is expected that the cubic molybdenum carbide can be functioned as an excellent cocatalyst to enhance the hydrogen-production activity of various photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…According to the deconvolution results, the Ti 2p spectrum of the composites is dominated by species in the Mo 6+ oxidation state, mainly MoO 3 with the presence of a small contribution of 5 + , 4 + and 2 + . The subcomponents detected by peak fitting at 229.3 eV and at 231.6 eV are attributed to Mo 3d 5/2 of MoO 2 , and of Mo 2 O 5 , respectively [ 43 , 44 , 45 ]. The existence of a noticeable percentage of MoO 2 and Mo 2 O 5 oxides on the surface of the composite together with the Mo 0 phase distinguishes the Ti + 10 wt % (Ti, Mo)C and Ti + 10 wt % (Ti, Mo)C/C composites.…”
Section: Resultsmentioning
confidence: 99%
“…The EEW process is a simple top‐down approach without some exquisite conditions for the preparation of metal nanocolloids. Representative advantages of EEW technique are room‐condition synthesis, green chemistry, cost‐effective, and mass‐productive 31 . Details of the EEW process were described in our previous reports 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…Representative advantages of EEW technique are roomcondition synthesis, green chemistry, cost-effective, and mass-productive. 31 Details of the EEW process were described in our previous reports. 32,33 Briefly, when the capacitor induces a pulse of high-density current to the metal wire, the wire evaporates immediately because of the high-density energy and then condenses back into a colloidal state in the liquid media.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%